Asia investment guide: an analysis of blue chips and dynamic companies in the world's fastest growing region (Euromoney Publications LondonGB, 1993)
Focuses on the blue chip companies of Singapore, Malaysia, the Philippines, Thailand, Indonesia and Hong Kong. Covers also, dynamic companies - these include companies with the biggest earnings per share growth in 1992 and those which have regional expansion plans.
Euromoney supplement September 1993